Determination of Height Based on Estimated Femur Length in Medan City - Shella, Remuqita; Parinduri, Abdul Gafar (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract : Identification checks are an important action to find out the identity of a person, other than living people, especially in the case of victims who have died or disappeared. The identification process used in the field of forensic anthropology is the anthropometric method, which measures one part of the body to determine the estimated height. The length of the inferior limbs has the most favorable correlation for human height. In this case, the femur is one of the parts of the body that is commonly used in height estimation. The femur section is the best parameter because it is in line with the anatomical structure of the body for the determination of height, which is useful in a clinical context. The researcher is interested in researching height based on femur length in FK UMSU students in the class of 2019. This research method is an analytical descriptive research with a cross-sectional design approach. The research subjects were 113 students of FK UMSU stambuk 2019, consisting of men and women who met the inclusion and exclusion criteria. Sampling technique using purposive sampling. The length of the femur has a correlation value that ranges from 0.382 to 0.534 (p≤0.001). The linear regression equation obtained showed a Standard Error of the Estimate (SEE) ranging from 0.164 to 0.272 (p≤0.001). There is a meaningful relationship between femur length and height, with such a strong correlation that height can be estimated by measuring femur length through linear regression equations.